The effect of the loyalty card program towards customers' attitudes and behavior in KUching, sarawak - Constance, Gerunsin. (UNIMAS, 2009)
The study is focusing on the customers’ effects in terms of behavior and attitudes through their observations towards the loyalty card program. The purpose is to make the retailers aware with this program either it is really effective or not to have this program in order to create loyalty among the customers in Kuching, Sarawak. However, the researcher is attempt to analyze the effectiveness of this program through measuring the cardholder of the loyalty card in terms of their commitment and determination after they have experienced with the whole involvement process. Instead of emphasizing on the loyalty effects alone, it is important to look at the different perspectives as well. The framework of this study has been altered in order to overlook the factors that affecting customers in performing their loyalty. Finally, the findings have shown that the impact of the loyalty card program is significant on customers’ attitudes and behavior in performing loyalty in Kuching, Sarawak.